Anaerobic endurance of dance sport athletes - Kuliś Szymon; Sienkiewicz-Dianzenza Edyta; Stupnicki Romuald (Sciendo, 2020)
Study aim: To assess the impact of an ordinary training week cycle lasting 6 months on the anaerobic endurance of dance sport athletes.